Identification of cross‐reactive B‐cell epitopes between Bos d 9.0101(Bos Taurus) and Gly m 5.0101 (Glycine max) by epitope mapping MALDI‐TOF MS. Issue 15 (26th July 2017) - Candreva, Ángela María; Ferrer‐Navarro, Mario; Bronsoms, Silvia; Quiroga, Alejandra; Curciarello, Renata; Cauerhff, Ana; Petruccelli, Silvana; Docena, Guillermo Horacio; Trejo, Sebastián Alejandro
Abstract : Exposure to cow's milk constitutes one of the most common causes of food allergy. In addition, exposure to soy proteins has become relevant in a restricted proportion of milk allergic pediatric patients treated with soy formulae as a dairy substitute, because of the cross‐allergenicity described between soy and milk proteins. We have previously identified several cross‐reactive allergens between milk and soy that may explain this intolerance. The purpose of the present work was to identify epitopes in the purified αS1‐casein and the recombinant soy allergen Gly m 5.0101 (Gly m 5) using an α‐casein‐specific monoclonal antibody (1D5 mAb) through two different approaches for epitope mapping, to understand cross‐reactivity between milk and soy. The 1D5 mAb was immobilized onto magnetic beads, incubated with the peptide mixture previously obtained by enzymatic digestion of the allergens, and the captured peptides were identified by MALDI‐TOF MS analysis. On a second approach, the peptide mixture was resolved by RP‐HPLC and immunodominant peptides were identified by dot blot with the mAb. Finally, recognized peptides were sequenced by MALDI‐TOF MS. This novel MS based approach led us to identify and characterize four peptides on α‐casein and three peptides on Gly m 5 with a common core motif. Information obtained from these cross‐reactive epitopes allows us to gain valuable insight into the molecular mechanisms of cross‐reactivity, to further develop new and more effective vaccines for food allergy.